MICROBIAL L-ASPARAGINASES AND STRATEGIES TO IMPROVE THEM - Achnafani, Dini; Sari, Aniska Novita (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
L-asparaginase is a type of hydrolase enzyme that has been used in anticancer treatment, mainly Acute Lymphoblastic Leukemia (ALL). L-asparaginase reduces the blood supply of L-asparagine needed by cancer cells to survive. The commercially approved L-asparaginase by the FDA originated from E. coli and E. chrysantemi. However, reports of immunogenic effects in more than 50% of cases due to the use of these enzymes have become the driving force for the need to explore other sources of L-asparaginase. In this review, various alternative sources of L-asparaginase other than these two microbes will be explained. Microbes from the group of Gram-positive bacteria, actinomycetes, and fungi produce L-asparaginase with a higher affinity for L-asparagine than L-glutamine. Protein engineering is an alternative strategy to produce L-asparaginase that is not recognized by antibodies to reduce the immune reaction. Besides, the fermentation process also needs to be considered to determine the appropriate substrate and bioprocess system to obtain the enzyme.